Identification of Suitable SSR Marker for Testing of Genetic Purity of Cotton Hybrids - Menka; Kumar, Amarendra; Yadav, S. K. (International Journal of Bio-resource and Stress Management, 2023)
India has the largest area in the World under cotton cultivation but the productivity is quite low due to inadequate supply of inputs including genetically pure seed to the farmers. Only high quality seeds of assured genetic purity can be expected to respond fully to all other inputs. Among the different quality aspect genetic purity is of utmost importance and enables farmers to exploit the full potential of hybrids. Grow Out Test (GOT) is mandatory to test the genetic purity of cotton hybrids as per the Indian minimum seed certification standards. But, it is labour intensive, tedious, time consuming and the expression of morphological characters may be influenced by environmental conditions. Alternatively, molecular markers could be used to assess the genetic purity to obtain quick, reliable and reproducible results. The genetic purity of two inters specific cotton hybrids namely, DCH 32 and RAHB 87 were assessed by microsatellite markers. Out of the 40 primers studied eight markers viz., (BNL 840, BNL 2590, BNL 3103, BNL 169, BNL 2544, BNL 2895, BNL 2572 and BNL 3441) were found polymorphic among the parents of both the hybrids. All the two hybrids were clearly distinguished from their selfed females and off types using these SSRs markers. Hence, these SSR markers can be used for the genetic purity testing of the cotton hybrids as it is accurate, rapid and without any influence of environment.